The Emergence and Scope of the Voice of Government: Propaganda, Civic Information, or Both? - Lee, Mordecai (Cambridge Scholars Publishing, 2023)
Nowadays, we all tend to be annoyed by bureaucracy and by propaganda, if only because both touch our daily lives. This book examines the intersection of those two subjects: external communications emanating from government agencies. When bureaucracies communicate with us directly or via the news media, are we being bombarded with self-serving propaganda or with helpful information to improve our lives? Perhaps it is a mash-up of both purposes?This book examines the scope, uses, and history of government communications. Topics of discussion include digital government, disaster communication, relations between the media and government, agency spokespersons, democratic reporting to the citizenry, wartime public relations (PR), and how US presidents and the US Congress treated bureaucratic PR. Several chapters are historical case studies, such as about an astronaut who became US Assistant Secretary of State for Public Affairs. In addition, two chapters examine President Nixon's record, while, in a more light-hearted vein, another presents the pop culture image of government spokespersons in movies. The book concludes with the origins of the academic study of external communications in public administration.